Serum adiponectin in women with polycystic ovary syndrome - Jahan, Iffat Ara; Morshed, Md Shahed; Banu, Hurjahan; Chowdhury, Emran Ur Rashid; Hasanat, Muhammad Abul (Bangladesh Journal of Medicine, 2023)
Background: An imbalance of different adipocytokines may play a role in the pathogenesis of PCOS. This study aimed to observe the association and diagnostic utility of adiponectinin PCOS and its manifestations. Methods: This cross-sectional study included 40 newly diagnosed females of reproductive age (18-40 years) with PCOS on the basis of international evidence-based guidelines and an equal number of matched healthy control. Along with clinical information, blood was drawn for biochemical and hormonal analysis. Glucose was measured by glucose oxidase, lipid by glycerol phosphate dehydrogenase peroxidase, all hormones by CMIA, and adiponectin by ELISA method. Insulin resistance was measured by homeostasis model assessment (HOMA-IR) and defined with a cut-off of 2.6. Results:Patients with PCOS had lower serum adiponectin than controls without significant differences even irrespective of body mass index status(ns for all). Adiponectin levels had no significant associations or correlations with any manifestations among patients with PCOS (ns for all). ROC curve analysis showed that serum adiponectin could not be used as a marker of PCOS. It was a poor marker of both metabolic syndrome [AUC (95% CI): 0.64 (0.46-0.81] and insulin resistance [AUC (95% CI): 0.61 (0.44-0.79)] in patients with PCOS. Conclusion: Our study failed to find any significant association between adiponectin and PCOS and its characteristics. Serum adiponectin could not be used as a marker of PCOS. It was a poor marker of insulin resistance and metabolic syndrome among patients with PCOS. Bangladesh J Medicine 2023; 34(3): 206-213